Declines in Peak Snow Water Equivalent and Elevated Snowmelt Rates Following the 2020 Cameron Peak Wildfire in Northern Colorado. Issue 6 (28th March 2023) - McGrath, Daniel; Zeller, Lucas; Bonnell, Randall; Reis, Wyatt; Kampf, Stephanie; Williams, Keith; Okal, Marianne; Olsen‐Mikitowicz, Alex; Bump, Ella; Sears, Megan; Rittger, Karl
Abstract: Wildfires are increasingly impacting high‐elevation forests in the western United States that accumulate seasonal snowpacks, presenting a major disturbance to a critical water reservoir for the region. In the first winter following the 2020 Cameron Peak wildfire in Colorado, the peak snow water equivalent in a high burn severity forest was 17%–25% less than nearby unburned sites. The loss of the forest canopy and a lower surface albedo led to an increasingly positive net shortwave radiation balance in the burned area, resulting in melt rates that were 82%–144% greater than unburned sites and snow disappearance occurred 11–13 days earlier. Late‐season snow storms temporarily buried soot, thus increasing the albedo and delaying melt‐out by an estimated 4 days per storm in our study area. While these storms temporarily reduce the higher melt rates imposed by wildfire impacts, SNOTEL measurements show that they occur non‐uniformly across the western U.S. Plain Language Summary: Wildfire activity has increased markedly in the western U.S., with megafires (>100, 000 acres) and high‐elevation fires becoming increasingly common. These fires are increasingly occurring in forests that accumulate substantial snowpacks and thus provide a reliable water resource for downstream populations. Following a fire, the loss of canopy can change how much snow accumulates and the rate and timing of its melting. Working in the 2020 Cameron Peak wildfire scar in Colorado, we found that a burned site accumulated less snow than unburned portions of the study area. The largest snowpack changes occurred in the spring, when snow in the burned site melted up to 144% faster and melted out 11–13 days earlier than unburned areas. The loss of tree canopy greatly increases the amount of solar energy that reaches the snow surface. Soot and debris from burned trees make the snow surface darker, resulting in more of this energy being absorbed. Late‐season snow storms were able to temporarily counteract some of these effects by burying the darker snow surface. As more and more of the western United States is fire‐impacted, it is essential to better understand and account for these impacts on this critical water reservoir for this region. Key Points: Peak snow water equivalent in the burned area was 17%–25% lower than paired unburned areas Snowmelt rates were 82%–144% greater at the burned site compared to unburned sites and snow disappearance occurred 11–13 days earlier Late‐season snow storms reset albedo and delayed melt‐out, thus regional variability in storm frequency can modulate melt rates in burned areas